Advances in electronic skin research: a bibliometric analysis - Xu, Shiyong; Yu, Xiaona; Chen, Jie; Jing, Yuan (Frontiers in Materials, 2023)
Background: E-skin (electronic skin) is an active research area in human-computer interaction and artificial intelligence. Methods: A bibliometric analysis was performed to evaluate publications in the E-skin field between 2000 and 2021 based on the Web of Science (WoS) databases. Results: A total of 4,954 documents were identified. A detailed overview of E-skin research was presented from aspects of productive countries/regions, institutions, journals, citations, highly cited papers, keywords, and emerging topics. With the emergence of new functional materials, structural design, 3D printing, and nanofabrication techniques, E-skin research has achieved dramatic progress after 2013. Scholars and institutions in China, the United States and South Korea are leading the way in E-skin research. Pressure sensor, strain sensor, and flexible electronics are the most focused directions at present and Internet of things is the most emerging topic. Conclusions: E-skin research has achieved dramatic progress but there is still quite a challenging task in practical applications. Manufacturing process simplification, cost reduction, functional integration, energy supply, and biocompatibility are vital for the future development of E-skin.